PENERAPAN SANKSI TERHADAP PELAKU TINDAK PIDANA ANAK YANG DIJADIKAN PEKERJA SEKS KOMERSIAL OLEH PENGADILAN NEGERI PEKANBARU - Sarah Dian Marsa; Emilda Firdaus; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
In the current era of globalization, the need for human life in all areas increased. Thus, each person will make every effort to meet these needs, not least if it has to commit criminal acts. Son is a creature of God Almighty and social beings, from conception until birth to have the right to life and freedom and protection that either of the parents, family, community, nation and state.Implementation of Sanctions Against the Crime of Child Prostitutes cite by District Court Judge Pekanbaru is the verdict should be able to impose a more severe punishment against the defendant so the defendant can get a deterrent effect because the child still has a long future. Both ruling given by the District Court Pekanbaru are not in accordance with the Child Protection Act No. 35 of 2014 due to the decision Pekanbaru District Court judge ruled that was too low for the defendant. The third concept is ideal in the imposition of sanctions for the crime of children into commercial sex work is with the aim of achieving justice, rule of law and social benefit for the community.Suggestions Writer, first suggested to the judge in order to impose a more severe punishment against the defendant so the defendant can get a deterrent effect because the child still has a long future. Because the goal of the law is that the law should reflect justice. Second, the judge hoped to be able to make a decision as it is in the Act. If the judge's decision is too low it will not be able to give deterrent effect to the perpetrators of child pengekspoitasi. Judges should always strive to improve ourselves. The third is expected that the implementation of the concept is ideal for the judge, the judge must be able to meet the three elements of justice, rule of law and social benefit for the community. Judges should add to the experience, and can sharpen the analysis in order to reach a decision that is considered unfair to the defendant and the public.Keywords: Implementation of Sanctions - Crime of the Child - Commercial Sex Workers